The understanding of Islamic management practices among Muslim managers in Malaysia - Sulaiman, Mohamed; Abdul Sabian, Nur Arfifah; Othman, Abdul Kadir (Canadian Center of Science and Education, 2014)
Islam is a comprehensive religion which covers every single aspect of human activity. Islam is not a religion that only focuses on the private life of individuals, but also covers and guides humans’ interaction and activities in their daily lives. Despite the comprehensiveness of the Islamic teachings, limited studies have been conducted to examine the practice of Islam in the management of business processes in Muslim organizations. Therefore, this paper aims to investigate the understanding of Muslim managers regarding Islamic management in their organization. The study utilizes a qualitative research design by means of in-depth interviews with the selected Muslim managers from the prominent Muslim organizations in Malaysia. The findings of this study indicate that Muslim managers in Malaysia have great understanding of Islamic management practices and they have implemented these practices in their organizations. However, there is a great opportunity for improvement in the future with regards to Islamic management practices. The implication of this study is also discussed.